Immunohistochemical assessment of possible anticancer effect mechanisms of 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)- 5,6,7-trichloro-1,3-tropolone in PDX models of lung cancer - E. F. Komarova; E. A. Lukbanova; E. A. Dzhenkova; A. S. Goncharova; E. V. Zaikina; S. V. Gurova; A. V. Galina; L. K. Kurbanova; M. V. Mindar; D. V. Khodakova; M. S. Gusareva; M. S. Zinkovich (Южно-Российский онкологический журнал, 2023)
Purpose of the study. Evaluation of the expression of immunohistochemical tumor markers Ki-67, b-catenin, Bcl-2, P53, connexin 32 and connexin 43 when using 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)-5,6,7-trichloro-1,3-tropolone in mice with xenographs of squamous cell lung cancer.Materials and methods. Subcutaneous PDX models of human squamous cell lung cancer were created in immunodeficient BALB/c Nude mice. A fragment of the patient’s tumor (3 × 3 × 3 mm) was implanted subcutaneously in the right thigh of a previously anesthetized mouse. 200 μl of 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)-5,6,7-trichloro-1,3-tropolone was administered orally using a probe in 12 doses once every 3 days. All animals were divided into groups depending on the tropolone doses: experimental groups 2–5 with doses of 0.0055, 0.055, 0.55 and 2.75 mg/g, respectively. The control group received 1 % starch gel which was tropolone carrier. The animals were euthanized 36 days after the start of the substance administration, and the tumor tissue was isolated and prepared for the IHC study according to the standard protocol. IHC reactions were performed using antibodies for Ki-67, b-catenin, Bcl-2, P53, connexin 32 and connexin 43.Results. Higher tropolone doses were associated with decreased expression of Ki-67, b-catenin, and the Bcl-2 protein, but increased expression of the P53 protein. The dosage of tropolone and expression of connexin 43 were directly proportional.Conclusion. Immunohistochemical analysis of expression of proteins in PDX models of human squamous cell lung cancer when using 2-(6,8-dimethyl-5-nitro-4-chloroquinoline-2-yl)-5,6,7-trichloro-1,3-tropolone showed the changes indicating its antitumor efficacy and suggesting a possible mechanism of action based on the activation of apoptosis.